Surveillance imaging in mantle cell lymphoma in first remission lacks clinical utility. Issue 4 (3rd April 2018) - Guidot, Daniel M.; Switchenko, Jeffrey M.; Nastoupil, Loretta J.; Koff, Jean L.; Blum, Kristie A.; Maly, Joseph; Flowers, Christopher R.; Cohen, Jonathon B.
Abstract: Mantle cell lymphoma (MCL) is a heterogeneous disease with high relapse rates. Limited data guide the use of surveillance imaging following treatment. We constructed a retrospective cohort from two academic institutions of patients with MCL who completed first-line therapy and underwent follow-up for relapse, analyzing the effect of surveillance imaging on survival. Of 217 patients, 102 had documented relapse, with 38 (37%) diagnosed by surveillance imaging and 64 (63%) by other methods. Relapse diagnosis by surveillance imaging had no significant advantage in overall survival from diagnosis date (hazard ratio [HR] = 0.80, p = .39) or relapse date (HR = 0.72, p = .22). Of 801 surveillance images, PET/CT had a positive predictive value (PPV) of 24% and number needed-to-scan/treat (NNT) of 51 to detect one relapse, and CT had a PPV of 49% and NNT of 24. For MCL after first-line therapy, relapse detection by surveillance imaging was not associated with improved survival and lacks clinical benefit.